2018
DOI: 10.1111/iju.13535
|View full text |Cite
|
Sign up to set email alerts
|

Local treatment for metastatic prostate cancer: A systematic review

Abstract: The potential oncological benefit for radical treatment in the setting of oligometastatic prostate cancer has been under investigation and is frequently discussed. We carried out a systematic review of English language articles using the Medline database (January 2000 to May 2017) to identify studies reporting local treatment in men with metastatic prostate cancer at diagnosis. Primary end-points were oncological outcomes, such as cancer-specific and overall mortality. Secondary end-points were non-oncological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
27
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 21 publications
0
27
0
4
Order By: Relevance
“…Dear Editor, Inoue et al reported an increased risk of secondary hematological neoplasms in patients with metastatic germ cell tumor receiving multiple regimens of chemotherapy. 1 Our group has already reported on the incidence of secondary hematological neoplasms in Japanese patients with germ cell tumor receiving chemotherapy. 2 In our series of 139 patients, three patients (2.2%) developed acute myeloid leukemia or myelodysplastic syndrome, of whom all had received a single first-line regimen of conventional chemotherapy.…”
Section: Re: Therapy-related Acute Myeloid Leukemia and Myelodysplastmentioning
confidence: 99%
See 4 more Smart Citations
“…Dear Editor, Inoue et al reported an increased risk of secondary hematological neoplasms in patients with metastatic germ cell tumor receiving multiple regimens of chemotherapy. 1 Our group has already reported on the incidence of secondary hematological neoplasms in Japanese patients with germ cell tumor receiving chemotherapy. 2 In our series of 139 patients, three patients (2.2%) developed acute myeloid leukemia or myelodysplastic syndrome, of whom all had received a single first-line regimen of conventional chemotherapy.…”
Section: Re: Therapy-related Acute Myeloid Leukemia and Myelodysplastmentioning
confidence: 99%
“…3 That study showed an overall survival benefit (hazard ratio 0.327 vs control) when RT was added to prostate treatment, which is in accordance with previous reports. 1 Similarly, in propensity score-matched analysis, there was a statistically significant difference in overall survival between patients treated with ADT and ADT plus RT.…”
mentioning
confidence: 91%
See 3 more Smart Citations